Gombrowicz's Kronos: The Pornography of Aging. (October 2013) - Oklot, Michal
<x content-type="archive" xml:space="preserve">Abstract</x> An attempt is made to sketch a strategy for reading Kronos (2013), Witold Gombrowicz's (1904–1969) recently published intimate journal, which he kept in the years 1952–1969. It treats Kronos as belonging to Gombrowicz's corpus, not merely as a literary sensation or an indiscretion, but as an important artistic and philosophical exhibit, which throws further light on Gombrowicz's preoccupation with the expression of the body and the existentialist concept of person as presence, one of his Nietzschean strategies for countering metaphysics and its ideal transcendence. The key concepts that bring together the artistic, the autobiographical/somatic, and the philosophical are pain and aging. This reading, in demonstration of the artistic unity of Gombrowicz's corpus, situates Kronos in the context of the novel Pornografia (1960) and the Diary (1953–1969), which share the major themes of aging and pain.